Characteristics of Vegan Corned Beef (Study of Soybean Paste Proportions : Gluten Flour and Lecithin Addition) - Marlinauli Manurung, Ruth; Rosida, Rosida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
This study aims to determine the proportion of soybean paste and gluten flour with the addition of soy lecithin on the characteristics of vegan corned beef. This research used a Completely Randomized Design (CRD) with a factorial pattern and three replications. Factor I is the proportion of soybean paste : gluten flour (65:35, 60:40, 55:45). Factor II is the addition of lecithin (0.25%, 0.50%, 0.75%). The data obtained were analyzed using ANOVA and continued with the Duncan Multiple Range Test (DMRT) at the 5% level. The results of the research show that there is a real interaction with the values ??of water content, hardness, emulsion stability, protein content and organoleptic tests. Vegan corned beef with soybean paste treatment: Gluten flour (55:45) with the addition of 0.75% lecithin is the best treatment which produces vegan corned beef with characteristics of 59.72% water content, 31.17% protein content, 17.85 N hardness, emulsion stability 1.90%, as well as a taste preference score of 3.28 (neutral), color 3.44 (neutral), and texture 4.04 (like).